Revision of the crocodilians from the Oligocene of Monteviale, Italy, and the diversity of European eusuchians across the Eocene-Oligocene boundary. Issue 2 (4th March 2019) - Macaluso, Loredana; Martin, Jeremy E.; Del Favero, Letizia; Delfino, Massimo
ABSTRACT: Crocodilian remains from the Oligocene fossil locality of Monteviale, northeastern Italy, have historically been referred to different genera, but all material was recently assigned to Diplocynodon cf. D. ratelii Pomel, 1847. The purpose of the present work is to clarify the systematics of the known crocodilian remains from Monteviale. The largest collection is housed in Padua, Italy, but museums in La Rochelle, France; Basel, Switzerland; and London, United Kingdom reposit crocodilian remains of uncertain provenance but which are clearly from either Monte Bolca or Monteviale. Radiogenic strontium isotope ratios were measured on the embedding lignite of those specimens to investigate their provenance. The material belongs to the genus Diplocynodon, but it clearly differs from D. ratelii because the nasal elements are excluded from the external nares. Diplocynodon from Monteviale shares the same general suture pattern of the skull with the two species D. tormis and D. muelleri. Diplocynodon muelleri and specimens from Monteviale are also congruent in terms of shape and proportion of the supratemporal fenestrae. However, a revision of D. muelleri is currently needed; thus, the Monteviale species is identified as Diplocynodon cf. D. muelleri . In order to examine the relationships of Diplocynodon from Monteviale, a phylogenetic analysis was carried out and points to a particularly close relationship among D. muelleri, D. tormis, and the Diplocynodon from Monteviale. The occurrence of Asiatosuchus in Monteviale is rejected, supporting the hypothesis of a reduction in crocodilian diversity around the Eocene-Oligocene boundary in Europe.